Penerapan Pembelajaran IPA Berdiferensiasi pada Kurikulum Merdeka - Nur Wahyuni; Dwi Baniati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to determine the application of natural science which is carried out in a differentiated manner. This study uses a qualitative method with a case study approach, and data analysis techniques using triangulation techniques that confirm data based on observations, interviews, and documentation. Researchers produced findings including the implementation of differentiated learning that had been successfully implemented by natural science teachers. Teachers use content differentiation, process differentiation, and product differentiation. Differentiated learning outcomes have a positive impact both in terms of teachers and students. Through differentiated learning the teacher feels happy because the students are more enthusiastic and involved, this is manifested in the form of products produced by students in very creative learning. However, the challenges received by the teacher at the process differentiation stage, the teacher still finds confusion when differentiating teaching materials that must be given to various students. Differentiated learning in the independent curriculum gives students autonomy to be able to express their learning abilities based on their potential and interests.